Investigation of Thermosiphoning Operation in Compound Parabolic Concentrating Solar Collector Integrated With Evacuated Flow Through Receiver - Francis Xavier, Jeffry Christopher (2018)
Although there are numerous studies to evaluate the performance of various designs of CPCs, there are very few papers to investigate the performance of a CPC collector in a tropical rainforest environment, such as the one experienced in Malaysia, where the proportion of diffuse solar radiation is high. Also, another motivation for this research is the lack of research on the incorporation of thermosiphoning as the propulsion energy for the working fluid of CPC collectors. Hence, this study aims to experimentally investigate the performance of a CPC collector in the tropical rainforest climate of Malaysia and the feasibility of using thermosiphoning as the propulsion energy of its working fluid. To achieve these objectives, an experimental test rig of the CPC collector, consisting of 3 evacuated flow through absorbers was set up at the Solar Research site of Universiti Teknologi PETRONAS, Malaysia. The performance of the CPC collector using Therminol-55 oil as the working fluid and the feasibility of employing thermosiphoning as the propulsion energy of its working fluid were determined by recording and analysing various parameters related to heat transfer. From the experimentation, it was determined that the concept of thermosiphoning was feasible to be employed in a CPC collector. Also, the oil outlet temperature in the CPC collector went up to 87.3°C on a day with low intensity of solar radiation and up to 132.7°C on a day with high intensity of solar radiation. Thus, the data collected suggested that the CPC collector can function effectively in the tropical rainforest climate of Malaysia. The expected thermal efficiency of the CPC collector is around 25% and the low efficiency is attributed to the high gap losses in the absorber tube. In addition, a Computational Fluid Dynamics (CFD) model was also developed for a single evacuated absorber tube of the CPC. The variation of the oil’s outlet temperature against time generated by the CFD simulation was comparable with the experimental data with Mean Absolute Percentage Error of 6.09 % and thus, the model was validated to estimate the oil temperature in the absorber tubes provided that the radiation data for a particular day is given as the input.